Breast self-examination: Resistance to change - Del Giudice, M. Elisabeth (College of Family Physicians of Canada, 2005)
OBJECTIVE: To investigate whether Canadian family practitioners routinely teach breast self-examination (BSE) after publication of the 2001 Canadian Preventive Health Task Force guideline advising them to exclude teaching BSE from periodic health examinations. DESIGN: Self-administered cross-sectional mailed survey. SETTING: Canada. PARTICIPANTS: A random sample of English-speaking general practitioners and physicians certified by the College of Family Physicians of Canada. MAIN OUTCOME MEASURES: Current and past BSE practices and opinions on the value of BSE. RESULTS: Response rate was 47.4%. Most respondents (88%) were aware of the new recommendations, yet only 16% had changed their usual practice of routinely teaching BSE. Most physicians agreed that before the recommendation they almost always taught BSE (74.3%). Only 9.5% agreed that physicians should follow the recommendation and not routinely teach BSE. A few also agreed that they now spend less time discussing BSE (25.7%) and that the recommendation has influenced them to stop teaching (12.4%) and encouraging (12.9%) women to practise BSE. Physicians who had changed their BSE practices were less likely to agree that BSE increases early detection of breast cancer and more likely to agree that BSE increases benign breast biopsies. They were also more likely to agree that screening mammography in women older than 50 decreases mortality from breast cancer. CONCLUSION: This survey, which assessed routine teaching of BSE, revealed poor adherence by Canadian family physicians to a well publicized evidence-based guideline update. Resistance to change could in part be attributed to a lack of knowledge of the supporting evidence, a lack of confidence in the evidence to date, and personal experiences with patients within their practices.